1983
DOI: 10.1093/clinchem/29.7.1396
|View full text |Cite
|
Sign up to set email alerts
|

Variations of 1-deoxyglucose(1,5-anhydroglucitol) content in plasma from patients with insulin-dependent diabetes mellitus.

Abstract: The concentration of 1-deoxyglucose(1,5-anhydroglucitol) in plasma from patients with insulin-dependent diabetes mellitus was measured by gas-liquid chromatography with an all-glass capillary column. Twenty-one plasma samples were obtained from 21 patients before insulin therapy, and 34 more from 13 patients receiving insulin therapy. 1-Deoxyglucose was generally not detectable in plasmas of diabetic patients before they received insulin; it was measurable in the patients who had received insulin, although its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…But further researches need to be carried out, and more evidence needs to be investigated to confirm this hypothesis. Plasma concentration of 1,5-anhydroglucitol decreased in diabetic patients has been confirmed [ 11 , 12 ]. In order to eliminate interferences, diabetes patients were excluded in our research.…”
Section: Discussionmentioning
confidence: 94%
“…But further researches need to be carried out, and more evidence needs to be investigated to confirm this hypothesis. Plasma concentration of 1,5-anhydroglucitol decreased in diabetic patients has been confirmed [ 11 , 12 ]. In order to eliminate interferences, diabetes patients were excluded in our research.…”
Section: Discussionmentioning
confidence: 94%
“…Based on these data, Japanese research groups in their studies have demonstrated a decrease in the concentration of 1,5-AG in serum in patients with hyperglycemia compared to patients in an euglycemic state. Studies have shown that measurements of 1,5-AG reflect glycemic status during the previous 48 h -2 weeks [15,16]. In addition, a gradual normalization of 1,5-AG values was demonstrated for patients responding to glucose lowering drug therapy [17].…”
Section: Introductionmentioning
confidence: 99%
“…1,5-anhydro-D-glucitol (1,5AG) is one of the main polyols in the human body [18,27,32]. 1,5AG is produced from 1,5-anhydro-D-fructose (1,5AF) by a 1,5AF-specific NADPH-dependent reductase [2,19], and it is involved in carbon starvation signaling in the regulation of glycogen metabolism [10,19,21,24,33].…”
mentioning
confidence: 99%